Integrasi Stem Dan Teknologi Digital Dalam Pendidikan Fisika Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa: Systematic Literature Review Dan Bibliometric Analysis (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2025)
21st-century physics education requires the development of students' critical thinking skills through innovative learning that is integrated with digital technology. This study aims to conduct a systematic review of the literature discussing the integration of STEM and digital technology in physics education and to perform a bibliometric analysis to map the topics and directions of research development in STEM-based physics learning. The research method employs a Systematic Literature Review (SLR) approach and bibliometric analysis by analyzing 12 articles obtained from the Scopus database using the keywords physics, education, critical thinking, and STEM over the past five years. Article selection was conducted using the PRISMA approach with the assistance of Rayyan AI, while bibliometric analysis was performed using VOSviewer. The research results indicate that the integration of STEM and digital technology has proven effective in enhancing students' critical thinking skills through contextual and problem-solving-based learning. Project-Based Learning (PjBL) emerged as the dominant learning model integrating digital technology to create an interactive learning environment. Bibliometric analysis identified four main clusters focused on the role of students as the center of learning and teachers as facilitators of digital learning innovation. These findings confirm that the integration of STEM and digital technology supports pedagogical transformation toward more modern and adaptive learning, providing a foundation for educators to implement effective learning approaches in developing 21st-century skills.
Keywords: STEM; physics education; critical thinking; systematic literature review; bibliometric analysis